AB0969 Conventional and biologic disease modifying anti-rheumatic drugs for osteoarthritis: a meta-analysis of randomised controlled trials. (12th June 2018) - Persson, M.S.M.; Sarmanova, A.; Doherty, M.; Zhang, W.
Abstract : Background: The role of inflammation in osteoarthritis (OA) is controversial. Some perceive OA as a reparative process where modest inflammation is secondary to largely biomechanical insult. 1 In contrast, others believe synovial inflammation to be a central driver of OA pain and progression. 2 This has encouraged randomised controlled trials (RCTs) of conventional and biologic disease modifying anti-rheumatic drugs (DMARDs) in OA. However, it is unknown whether these treatments that are primarily used for rheumatoid arthritis are effective for OA. Objectives: To examine the efficacy of DMARDs, including biologics, in people with symptomatic OA. Methods: A systematic literature search was conducted (to November 2017) for placebo-controlled RCTs of DMARDs in OA. Data extraction and Cochrane's risk of bias assessments were conducted independently by two reviewers (MP, AS). Pain relief at treatment peak time-point was combined using a random-effects meta-analysis. All DMARDs were pooled and sensitivity analysis was undertaken for high-quality trials and subgroup analyses for DMARD type, biologic target, joint site, OA subtype, and publication type. Results: Eleven RCTs (n=1205), including six (n=757) for conventional and five (n=448) for biologic DMARDs, were included in the meta-analysis (7 full texts, 4 abstracts). Overall, conventional and biologic DMARDs were marginally superior to placebo. However, statistical superiority was not observed in high-quality studies (table 1) or subgroup analysis for conventional or biologic DMARDs separately (figure 1). Furthermore, no differences were observed between erosive versus non-erosive hand OA, hand versus knee OA, anti-IL1 versus anti-TNF biologics, or full text versus abstract-only publications (table 1). Conclusions: No significant pain relief was observed from either conventional or biologic DMARDs compared to placebo. Combining all DMARDs gave statistical separation from placebo, but this was below the minimal clinically important difference threshold (0.5 SD) used in the UK. 3 Furthermore, the analysis is based on peak time point for the intervention, so even at their most effective timepoints these treatments do very little over placebo. Lack of efficacy of DMARDs supports the perspective that inflammation is not an important driver for OA pain and differs fundamentally from that in rheumatoid arthritis. References: [1] Felson DT. Osteoarthritis as a disease of mechanics. Osteoarthritis and cartilage. 2013;21(1):10–15. [2] Robinson WH, et al. Low-grade inflammation as a key mediator of the pathogenesis of osteoarthritis. Nature Reviews Rheumatology. 201601 Oct;12(10):580–92. [3] NICE. Osteoarthritis: Care and management in adults [CG177]201416/10/2015. Disclosure of Interest: None declared